Genomic Testing in Localized Prostate Cancer Can Identify Subsets of African Americans With Aggressive Disease. (2nd September 2022) - Awasthi, Shivanshu; Grass, G Daniel; Torres-Roca, Javier; Johnstone, Peter A S; Pow-Sang, Julio; Dhillon, Jasreman; Park, Jong; Rounbehler, Robert J; Davicioni, Elai; Hakansson, Alex; Liu, Yang; Fink, Angelina K; et al.
Abstract: Background: Personalized genomic classifiers have transformed the management of prostate cancer (PCa) by identifying the most aggressive subsets of PCa. Nevertheless, the performance of genomic classifiers to risk classify African American men is thus far lacking in a prospective setting. Methods: This is a prospective study of the Decipher genomic classifier for National Comprehensive Cancer Network low- and intermediate-risk PCa. Study-eligible non–African American men were matched to African American men. Diagnostic biopsy specimens were processed to estimate Decipher scores. Samples accrued in NCT02723734, a prospective study, were interrogated to determine the genomic risk of reclassification (GrR) between conventional clinical risk classifiers and the Decipher score. Results: The final analysis included a clinically balanced cohort of 226 patients with complete genomic information (113 African American men and 113 non–African American men). A higher proportion of African American men with National Comprehensive Cancer Network–classified low-risk (18.2%) and favorable intermediate-risk (37.8%) PCa had a higher Decipher score than non–African American men. Self-identified African American men were twice more likely than non–African American men to experience GrR (relative risk [RR] = 2.23, 95% confidence interval [CI] = 1.02 to 4.90; P = .04). In an ancestry-determined race model, we consistently validated a higher risk of reclassification in African American men (RR = 5.26, 95% CI = 1.66 to 16.63; P = .004). Race-stratified analysis of GrR vs non-GrR tumors also revealed molecular differences in these tumor subtypes. Conclusions: Integration of genomic classifiers with clinically based risk classification can help identify the subset of African American men with localized PCa who harbor high genomic risk of early metastatic disease. It is vital to identify and appropriately risk stratify the subset of African American men with aggressive disease who may benefit from more targeted interventions.